2019
DOI: 10.7824/rbh.v18i1.618
|View full text |Cite
|
Sign up to set email alerts
|

Determinação da dose de controle de Urochloa decumbens pela aplicação de glyphosate

Abstract: A espécie Urochloa decumbens é uma importante planta daninha de culturas agrícolas devido à alta capacidade adaptativa e dificuldade de manejo. A presença dessas plantas em áreas de produção agrícola pode gerar problemas quando compete por água, luz e nutrientes, além de atuar como hospedeira de pragas e patógenos comuns à cultura e interferir na colheita. O trabalho objetivou avaliar doses de controle de plantas de U. decumbens pela aplicação de glyphosate. Foram realizados três experimentos, em casa de veget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
0
4
0
4
Order By: Relevance
“…Therefore, under-doses of glyphosate do not completely stop the EPSPS activity (Pincelli-Souza et al, 2020), which justifies the lower mortalities under lower glyphosate doses. Moraes et al (2019) verified the total mortality of U. decumbens plants at 21 DAA under doses over 360 g a.e. ha -1 .…”
Section: Resultsmentioning
confidence: 58%
“…Therefore, under-doses of glyphosate do not completely stop the EPSPS activity (Pincelli-Souza et al, 2020), which justifies the lower mortalities under lower glyphosate doses. Moraes et al (2019) verified the total mortality of U. decumbens plants at 21 DAA under doses over 360 g a.e. ha -1 .…”
Section: Resultsmentioning
confidence: 58%
“…However, the dose of 86.40 g ae ha -1 reduced the biomass by 35.22% in the 2nd cut, with a production of 1.14 g pot -1 . Moraes et al (22) conducted an assessment at 21 days after application (DAA) of a less concentrated spray solution volume (200 L ha -1 ) and found that a dose between 30 and 62 g ae ha -1 of the herbicide reduced the growth of U. decumbens by 50%, without characterizing symptoms of phytotoxicity. Carbonari et al (23) assessed the effects of the application of different underdoses of glyphosate on the growth of sugarcane (Saccharum officinarum) and observed that the application of doses higher than 72 g ae ha -1 significantly compromised biomass production.…”
Section: Resultsmentioning
confidence: 99%
“…ha -1 , e superiores, foram suficientes à inviabilização produtiva da forrageira, evidenciado nos cortes 3 e 4. Entretanto, Moraes et al (2019) utilizando volume de calda menos concentrado (200 L ha -1 ) constataram que a dose 62 g e.a. ha -1 reduziu em 50% o crescimento das plantas de Urochloa decumbens, ainda, possibilitando produção forrageira.…”
Section: -----------Corte 1 ----------------------Corte 2 -----------unclassified
“…Deste modo, doses inferiores a 90 g e.a.ha -1 não são suficientes aos sintomas de amarelecimento, necrose foliar e, consequentemente, morte da planta. Moraes et al (2019), constataram morte total das plantas aos 21 dias após aplicação, para doses superiores a 360 g e.a. ha -1 .…”
Section: -----------Corte 1 ----------------------Corte 2 -----------unclassified